Sorting of GPI-anchored proteins at the trypanosome surface is independent of GPI insertion signals - Thomas Henry Miller; Sabine Schiessler; Ella Maria Rogerson; Catarina Gadelha (The Cell Surface)
The segregation of glycosylphosphatidylinositol-anchored proteins (GPI-APs) to distinct domains on the plasma membrane of eukaryotic cells is important for their correct cellular function, but the mechanisms by which GPI-APs are sorted are yet to be fully resolved. An extreme example of this is in African trypanosomes, where the major surface glycoprotein floods the whole cell surface while most GPI-APs are retained in a specialised domain at the base of the flagellum. One possibility is that anchor attachment signals direct differential sorting of proteins. To investigate this, we fused a monomeric reporter to the GPI-anchor insertion signals of trypanosome proteins that are differentially sorted on the plasma membrane. Fusions were correctly anchored by GPI, post-translationally modified, and routed to the plasma membrane, but this delivery was independent of retained signals upstream of the ω site. Instead, ω−minus signal strength appears key to efficacy of GPI addition and to GPI-AP cellular level. Thus, at least in this system, sorting is not encoded at the time of GPI anchor addition or in the insertion sequence retained in processed proteins. We discuss these findings in the context of previously proposed models for sorting mechanisms in trypanosomes.